Electrode movement prevention - an animal model - Masopust, V; Petríková, I; Mlček, M; Holubová, J; Rokyta, R; Fricová, J; Janoušková, K (Physiological research, 2019)
Electrode migration is the most common complication of spinal cord stimulation (SCS). The problem of longitudinal migration has already been solved, but lateral migration remains the most common current complication. The present article describes new electrodes fixation opportunities for the reduction of lateral migration in SCS. The pig was chosen as an animal model to illustrate a new protocol of electrode fixation for the control of lateral and longitudinal migration. The displacement of the electrode was measured using two different optical methods: the digital image stereo-correlation and the digital image processing methods. Fixation with two anchors has always considerably reduced electrode displacement and when fixation is done with two anchors and a loop then lateral migration is reduced by 62.5 % and longitudinal migration is reduced by 94.1 %. It was shown that the results are significantly different at the alpha=0.001 significance level. Based on a statistical evaluation it is possible to state that the differences between experimental results obtained for three different protocols of lead fixation are statistically significant and we can recommend the new fixation method for common practice.
Keywords: implantované elektrody; Foreign-Body Migration; Models, Animal; Swine; migrace cizích těles; Animals; Electrodes, Implanted; modely u zvířat; zvířata; prasata; počítačové zpracování obrazu; Image Processing, Computer-Assisted